Reduction of heart failure guideline‐directed medication during hospitalization: prevalence, risk factors, and outcomes. (7th July 2022) - Palin, Victoria; Drozd, Michael; Garland, Ellis; Malik, Anam; Straw, Sam; McGinlay, Melanie; Simms, Alexander; Gatenby, V. Kate; Sengupta, Anshuman; Levelt, Eylem; Witte, Klaus K.; Kearney, Mark T.; et al.
Abstract: Aims: Optimal management of heart failure with reduced ejection fraction (HFrEF) includes titration of guideline‐directed medical therapy (GDMT) to the highest tolerated dose within the licensed range. During hospitalization, GDMT doses are often significantly altered, although it is unknown whether the cause of hospitalization influences this. Methods and results: We recruited 711 people with stable HFrEF from specialist heart failure clinics and prospectively assessed events occurring during first unplanned hospitalization. Dose changes of ACE inhibitors or angiotensin receptor blockers (ACEi/ARB), beta‐blockers, mineralocorticoid receptor antagonists, and loop diuretics were recorded during 414 hospitalizations, categorized as due to decompensated heart failure, other cardiovascular causes, infection, or other non‐cardiovascular causes. Most hospitalizations resulted in no change to GDMT. ACEi/ARB dose was reduced in 21% of hospitalizations and was more common during non‐cardiovascular hospitalization (25.4% vs. 13.9%; P  = 0.005). ACEi/ARB dose reduction was associated with older age and lower left ventricular ejection fraction at study recruitment, and poorer renal function, lower systolic blood pressure, higher serum potassium, and less frequent care from a cardiologist during admission. People experiencing ACEi/ARB reduction had worse age‐adjusted survival after discharge, without differences in heart failure re‐hospitalization. De‐escalation of beta‐blockers occurred in 8% of hospitalizations, most often due to other non‐cardiovascular causes; this was not associated with post‐discharge survival or re‐hospitalization with heart failure. Conclusions: De‐escalation of HFrEF GDMT is more common during non‐cardiovascular hospitalization and for ACEi/ARB is associated with reduced survival. Post‐discharge care plans should include robust plans to consider re‐escalation of GDMT in these cases.